2018
DOI: 10.1111/jcmm.13613
|View full text |Cite
|
Sign up to set email alerts
|

Chemical, biochemical, preclinical and clinical studies of Ganoderma lucidum polysaccharide as an approved drug for treating myopathy and other diseases in China

Abstract: Ganoderma lucidum is an edible medicinal mushroom known as “Lingzhi” in China and “Reishi or Manetake” in Japan. It is a highly prized vitality‐enhancing herb for more than 2000 years. G. lucidum polysaccharide (GLPS) has been identified as one of the major bioactive components and developed into a drug named “Ji 731 Injection” in China since 1973. The large‐scale production of the drug began in 1985 and approved by the Chinese FDA as “Polysaccharidum of G. lucidum Karst Injection” (Ling Bao Duo Tang Zhu She Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(48 citation statements)
references
References 47 publications
0
47
0
1
Order By: Relevance
“…Ganoderma lucidum (G. lucidum) is a medicinal mushroom that has been used in East Asian countries for over 2000 years [3][4][5] . A substantial number of preclinical and clinical studies have reported that G. lucidum has numerous pharmacological effects, including antioxidant, hypoglycemic, immune-regulatory, anti-diabetic, and anti-cancerous [5][6][7][8][9][10] . Many studies have demonstrated that GLP is one of the main bioactive components responsible for anti-cancer effects of G. lucidum 3,5 .…”
Section: Introductionmentioning
confidence: 99%
“…Ganoderma lucidum (G. lucidum) is a medicinal mushroom that has been used in East Asian countries for over 2000 years [3][4][5] . A substantial number of preclinical and clinical studies have reported that G. lucidum has numerous pharmacological effects, including antioxidant, hypoglycemic, immune-regulatory, anti-diabetic, and anti-cancerous [5][6][7][8][9][10] . Many studies have demonstrated that GLP is one of the main bioactive components responsible for anti-cancer effects of G. lucidum 3,5 .…”
Section: Introductionmentioning
confidence: 99%
“…The relatively inexpensive polysaccharides from the traditional Chinese herbs should be useable for the development of novel therapeutic agents, functional food, or adjuvants for preventing or treating different pathological conditions as those fungal polysaccharide-based drugs approved and used in China. 6,[121][122][123][124][125][126]…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Colourless needles; m.p. 157.9-160.4 C; [a] 23 D +6.44 (c 0.06, MeOH); UV (MeOH) l max (log 3): 241.60 (3.23); 1 H NMR data (Table 1); 13 C NMR data ( (10) , g ¼ 90 , V ¼ 726.04(5)Å 3 , T ¼ 100(2) K, space group P2 1 , Z ¼ 2, m(CuKa) ¼ 0.736 mm À1 , 7540 reections measured, 2510 independent reections (R int ¼ 0.0263). The nal R 1 values were 0.0327 (I > 2s(I)).…”
Section: Extraction and Isolationmentioning
confidence: 99%
“…8 All these efforts have illuminated and enriched the chemical prole of Ganoderma secondary metabolites, which has made it possible for Ganoderma to be developed as a regular drug rather than as a dietary supplement. 9,10 Sesquiterpenoids are the most abundant type of secondary metabolites in mushrooms. 11 However, in contrast to the attention that has been paid on the triterpenes, research on sesquiterpenes from Ganoderma fruiting bodies is still unfolding.…”
Section: Introductionmentioning
confidence: 99%